Interferons Increase Cell Resistance to Staphylococcal Alpha-Toxin - Yarovinsky, Timur O. (American Society for Microbiology (ASM), 2008)
Many bacterial pathogens, including Staphylococcus aureus, use a variety of pore-forming toxins as important virulence factors. Staphylococcal alpha-toxin, a prototype β-barrel pore-forming toxin, triggers the release of proinflammatory mediators and induces primarily necrotic death in susceptible cells. However, whether host factors released in response to staphylococcal infections may increase cell resistance to alpha-toxin is not known. Here we show that prior exposure to interferons (IFNs) prevents alpha-toxin-induced membrane permeabilization, the depletion of ATP, and cell death. Moreover, pretreatment with IFN-α decreases alpha-toxin-induced secretion of interleukin 1β (IL-1β). IFN-α, IFN-β, and IFN-γ specifically protect cells from alpha-toxin, whereas tumor necrosis factor alpha (TNF-α), IL-6, and IL-4 have no effects. Furthermore, we show that IFN-α-induced protection from alpha-toxin is not dependent on caspase-1 or mitogen-activated protein kinases, but requires protein synthesis and fatty acid synthase activity. Our results demonstrate that IFNs may increase cell resistance to staphylococcal alpha-toxin via the regulation of lipid metabolism and suggest that interferons play a protective role during staphylococcal infections.